Education for girls in Ireland: secondary and vocational curricular provision 1930–1960. Issue 1 (2nd January 2016) - Clarke, Marie
Abstract : A challenge for historians of education is to explain the ways in which the development of education has been a gendered process. The literature tends to focus on primary and secondary schools; the role played by religious orders; the experiences of female teachers; ideological influences on curriculum; and the preparation of young girls for their role in society. Few historians, however, have examined vocational education and the impact of its 'social efficiency' orientation on girls. The literature that exists tends to treat both systems separately, and little effort has been made to compare the impact of both systems on girls' opportunities within the society in which they lived. This omission in the literature is significant as such a comparison facilitates insights regarding state policies and priorities for the education of girls, the impact of social class, and national and local circumstances. This article compares both systems of education in Ireland and their impact on girls during the period 1930–1960.